UM REPENSAR SOBRE AS PRÁTICAS DE ESCRITA ESCOLAR: EM EVIDÊNCIA O 5º E O 6º ANO DO ENSINO FUNDAMENTAL - Novatzki, Yara Fernanda (2015)
The main purpose of this research is to diagnose and analyze about how writing studies have being developed during two different stages of the learning process, what are the 5th and the 6th grade in two different public schools at Parana State country side. In order to accomplish our goal, the following objectives were the references of our research: 1) Observing the level of domain of language and speech on its written variety trough the student’s text production. 2) Discussing the leading difficulties from the point of view of teachers and pedagogic team; 3) Comparing the point of view of the teachers and pedagogic team; 4) Comparing the results reached on the item “3” with the analysis of the student’s text production; 5) Identifying and to analyze the most significant aspects detected during the transition from the beginning school grades to the ending school grades. On this matter, we tend to create a theoretical discussion showing how changes happened along the evolution of the writing cultures, and also evolution of the language and speech have being affected the understanding of those terms itself in the current modernity period, approaching some consensus and contradictions stablish on the educational system. In order to support our theoretical discussions, we have taken account the production of the following authors: Pinto (2012;2013;2014); Austin (1962); Rajagopalan (2003; 2013); Britto (2003), and others. The methodology adopted in this research is predominantly qualitative, as discussed by Lüdke & Andre (1986), and Oliveira (2012), because the tools and the analysis procedures used during the research are similar to main discussions we develop, what are: observation inside the classrooms, interview with teachers and pedagogic team and also student’s writing production analysis. It is important to enlighten that this study seek to contribute to change the way some teaching methods are developed inside the schools because, once the educational challenges are many and the number of illiterate people is considerable, what affect directly the educational system, a reflection and an analysis of that context is imperative, mostly because of the economic, cultural, social, technological development seen in the society.